Educational data modelling using curve fitting and average uniform algorithm. (2019) - Alazzam, Azmi; Al-Omar, Ban
One of the most widely used techniques in data modelling is curve fitting. Curve fitting is the process of creating a curve or a function that will model the data to be analysed. Often times the resultant curve will not pass through all the data points, this is why it is called a best-fit curve for the data. In this paper, we propose a curve fitting quadratic function that is used to model educational data. The resultant model is then used to predict one or more output variables based on different values for input variables. In order to optimise the parameters for the quadratic function, the proposed AUA algorithm is used. The AUA is a metaheuristic optimisation that can be used to optimise a wide variety of continuous functions (linear, nonlinear, convex and non-convex). The AUA algorithm is used to find the optimal values for the coefficients of the quadratic function. Moreover, the optimal values for these coefficients are found using the classical derivative method for the sake of comparison.